Caracterização agronômica e morfofisiológica de grama-tapete adubada com dejeto líquido de suínos - Brustolin, Karen Döering (2012)
In seeking an alternative to the excess pig slurry (PS), coupled with the need to increase the productivity of pastures, this study was conducted to evaluate the performance of a naturalized pasture carpet grass (Axonopus affinis Chase) fertilized with this residue as a source of nitrogen (N). We evaluated the production, chemical composition and floristic, and morphophysiological aspects of pasture due to increasing doses of PS calculated to provide 100, 200, 300, 400 and 500 kg N/ha/year, a positive control (200 kg N/ha/year in the form of ammonium nitrate, AN) and a negative one (no nitrogen fertilization). The experiment was conducted in Chapecó, Santa Catarina, in Oxisol, between 2008 and 2010. The pasture was maintained without grazing, and subjected to cuts in the first five years and six cuts in the second year, with removal of cut plant material. Nitrogenous fertilizers (PS and NA) were fractionated into four applications, which occurred after pasture cuttings. On the average of two years, it was applied 51, 102, 153, 204 and 255 m³/ha/year PS, corresponding to doses of N. The annual production of dry matter (DM) increased linearly with the dose of PS, from 2,598 to 7,718 kg DM/ha (2008-09) and 4,310 to 12,321 kg DM/ha (2009-10), an increase 16.5 and 38.6 kg of DM/m³ PS/ha, respectively. Doses of PS did not differ as for the nitrogen utilization agronomic efficiency (14.9 kg DM/kg N), which was 45% lower than that obtained with ammonium nitrate (27.2 kg DM/kg N). The average efficiency index of PS was 0.63, ranging from 0.38 (January/2010) to 0.96 (October/2010). The fertilization with PS and NA reduced the percentage of spontaneous legumes in the pasture, without affecting the levels of acid detergent fiber (39.3%) and neutral detergent fiber (67.3%). The crude protein content varied between treatments in only three cuts, with the highest value (16%) in the treatment without nitrogen fertilization. The leaf area index, tiller density, leaf length, and height canopy and reproductive increased linearly with doses of PS.